School-Based Financial Management in Improving the Quality of Junior High School Education in North Penajam Paser - Sripeni Sripeni; Nurlaili Nurlaili; Yudo Dwiyono (EduLine: Journal of Education and Learning Innovation, 2024)
This research analyzes the relationship between school-based financial management and the quality of educational services in secondary schools in Penajam Paser Utara. A qualitative approach using a case study method is employed to gain an in-depth understanding. Primary and secondary data were collected through interviews with school principals, treasurers, and teachers. Data analysis was conducted using an interactive model, involving organization, correlation, reduction, presentation, and conclusion drawing. The findings indicate that financial planning begins by identifying the sources of school income, such as Operational Assistance for Schools, Regional Operational Assistance for Schools, School Canteen, Endowments, School Housing Assets, and School Cooperatives. The formulation of the School Budget Plan is carried out through meetings to develop school programs. Fund allocation takes into account priority programs, and the organization of financial management involves consensus in forming personnel for school financial execution. School principals build effective relationships among personnel through the delegation of tasks. The implementation of school-based financial management involves expenditure procedures aligned with planning and transaction recording for accountability. Supervision is carried out through monthly financial report examinations, appreciation for successful actions, and accountability through accountability letter reports and audit results. Financial reporting and accountability are publicized on the school information board to demonstrate the overall effectiveness and accountability of the financial management process.